Pain severity during functional activities in individuals with patellofemoral pain: A systematic review with meta-analysis. Issue 5 (May 2022) - Glaviano, Neal R.; Bazett-Jones, David M.; Boling, Michelle C.
Abstract: Objectives: Patellofemoral pain (PFP) is a common lower extremity condition that results in pain during functional tasks. Currently, it is unknown the extent to which differences in pain levels exist in individuals with PFP compared to asymptomatic controls during functional task and if pain differ across various functional tasks. The purpose of this systematic review and meta-analysis is to evaluate pain levels between individuals with PFP and asymptomatic controls and compare pain severity across various functional tasks. Design: Systematic review. Methods: OVID, SPORTSDiscus, CINAHL, Web of Science and Embase were searched for studies that included PFP and asymptomatic controls with pain assessed during a functional task. Pooled pain scores mean with 95% confidence intervals were calculated between groups across 11 functional tasks. Standardized mean differences (SMD) were calculated based on Hedge's g effect sizes. Tasks whose SMD 95% confidence intervals were non-overlapping were considered significantly different. Results: 28 articles were included for data analysis. Pain was greater across 10 tasks (SMD = 1.52–6.08) in individuals with PFP compared to the asymptomatic controls with an average SMD of 2.45. Running and star excursion balance testing resulted in greater pain than walking. Limited evidence showed greater pain in sitting than seven other tasks. Conclusions: Moderate evidence exists for greater pain levels in individuals with PFP compared to asymptomatic controls in functional tasks. Pain was greater during running and star excursion balance compared to walking. Clinicians should assess knee pain before and after functional tasks to improve our understanding of patient specific pain experiences.